2020
DOI: 10.1017/s0954579420000814
|View full text |Cite
|
Sign up to set email alerts
|

Early behavioral profiles elucidating vulnerability and resiliency to later ASD outcomes

Abstract: Infant siblings of children with autism spectrum disorder (ASD) exhibit greater heterogeneity in behavioral presentation and outcomes relative to infants at low familial risk (LR), yet there is limited understanding of the diverse developmental profiles that characterize these infants. We applied a hierarchical agglomerative cluster analysis approach to parse developmental heterogeneity in 420 toddlers with heightened (HR) and low (LR) familial risk for ASD using measures of four dimensions of development: lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 82 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…Membership in the Lost Diagnosis group was predicted at Time 1 only by a low level of IJA. Greater expressive language skills (likely reflecting better representational and communication skills) and lower levels of RRB (possibly reflecting greater attentional and cognitive flexibility) may function as resiliency factors ( 47 ). By Time 2, predictors of membership in the Lost Diagnosis group expanded to include all three variables, which is not surprising given that 74% of the children in this group were diagnosed with ASD at Time 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Membership in the Lost Diagnosis group was predicted at Time 1 only by a low level of IJA. Greater expressive language skills (likely reflecting better representational and communication skills) and lower levels of RRB (possibly reflecting greater attentional and cognitive flexibility) may function as resiliency factors ( 47 ). By Time 2, predictors of membership in the Lost Diagnosis group expanded to include all three variables, which is not surprising given that 74% of the children in this group were diagnosed with ASD at Time 2.…”
Section: Discussionmentioning
confidence: 99%
“…Since joint attention limitations are often observed in young children with ASD ( 45 ) and joint attention skills strongly predict early language development ( 46 ) as well as later pragmatic communication skills ( 41 ), we examined Time 1 and Time 2 initiation of joint attention (IJA) behavior as predictors of Time 3 diagnostic classification. An IJA composite variable was derived using the sum of ADOS ratings from three items: Initiation of Joint Attention, Showing , and Giving ( 47 ). To account for differences across the ADOS Toddler Module and Module 1 in the range of item ratings and the operational definitions of those ratings, recoding of items was necessary to align item ratings across modules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous literature (Landa et al, 2012), ASD diagnosis at 36 months of age correlated with class membership, with the 55.6% of ASD children being represented in overall developmental slowing class. More interestingly, a recent study showed that children with an accelerated development in motor, cognitive, and language development from 6 to 36 months of age are "resilient" to the development of ASD (Landa et al, 2020).…”
Section: The Predictive Role Of Language Trajectories On Asd Symptomsmentioning
confidence: 99%
“…Although a direct assessment of language and produced gestures development may have been a valid alternative, parental reports are particularly suitable to be used with toddlers in the early stages of language acquisition (Sachse & Von Suchodoletz, 2008). In addition, behavioral studies should be conducted to assess the developmental status of gestures (Landa et al, 2020).…”
Section: The Predictive Role Of Language Trajectories On Asd Symptomsmentioning
confidence: 99%